Can Universities be a Gleam of Hope During COVID-19? Entrepreneurial Intentions Approach for Academia in Pakistan - Li, Guohao; Pervaiz, Sabeeh; He, Qi (Frontiers in Education, 2021)
COVID-19 pandemic has affected many countries' economics. One of its substantial consequences is job deficit and the need for time to train our students to be job creators rather than job seekers to support the economies. This research aimed to examine universities' role in students' attitude development towards entrepreneurship by analyzing the impact of locus of control, extracurricular activities, and curriculum on entrepreneurial intention among Pakistan's university students. This study collected data from 536 students across 15 universities in Pakistan through a weblink questionnaire. SPSS and AMOS were used to test the theoretical model. Results confirmed that locus of control positively affects entrepreneurial intentions and is the strongest predictor among the other two variables. Extracurricular activities positively affect entrepreneurial intentions, and curriculum is also positively affecting entrepreneurial intentions. This study concluded that entrepreneurial education and acquaintance are essential in bringing entrepreneurial intentions among students. Locus of control is found to be the most substantial element in developing entrepreneurial intentions among students. In enterprising, only our educational institutions can play a vital role by dynamically participating through their efficient and proficient curricula, skilled and experienced faculty, and locus of control by offering a blend of their curricular and co-curricular activities.